Pain in cervical dystonia: mechanisms, assessment and treatment. (3rd October 2021) - Rosales, Raymond L.; Cuffe, Lorraine; Regnault, Benjamin; Trosch, Richard M.
ABSTRACT: Introduction: In patients with cervical dystonia (CD), pain is a major contributor to disability and social isolation and is often the main reason patients seek treatment. Surveys evaluating patient perceptions of their CD symptoms consistently highlight pain as a troublesome and disabling feature of their condition with significant impact on daily life and work. Areas covered: In this article, the authors review the epidemiology, assessment, possible mechanisms and treatment of pain in CD, including a meta-analysis of randomized controlled trial data with abobotulinumtoxinA. Expert opinion: Mechanisms of pain in CD may be muscle-based and non-muscle based. Accumulating evidence suggests that non-muscle-based mechanisms (such as abnormal transmission and processing of nociceptive stimuli, dysfunction of descending pain inhibitory pathways as well as structural and network changes in the basal ganglia, cortex and other areas) may also contribute to pain in CD alongside prolonged muscle contraction. Chemodenervation with botulinum toxin is considered the first-line treatment for CD. Treatment with botulinum toxin is usually effective, but optimization of the injection parameters should include consideration of pain as a core symptom in addition to the motor problems